2010
DOI: 10.1021/nn101908e
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Pathway Toward a Superb Gene Delivery System: Programming Structural and Functional Diversity into a Supramolecular Nanoparticle Library

Abstract: Nanoparticles are regarded as promising transfection reagents for effective and safe delivery of nucleic acids into specific type of cells or tissues providing an alternative manipulation/therapy strategy to viral gene delivery. However, the current process of searching novel delivery materials is limited due to conventional low-throughput and time-consuming multistep synthetic approaches. Additionally, conventional approaches are frequently accompanied with unpredictability and continual optimization refineme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
133
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 41 publications
0
133
0
Order By: Relevance
“…Microfluidic devices promise a broad range of biomedical and chemical applications due to their potentials of small volume requirement, short analysis and diagnostic time, high sensitivity, and high throughput analysis [1][2][3]. Recently, particular attention has been paid to droplet-based (digital) microfluidic devices since droplets isolated in immiscible oil or air can be free from cross-contamination and dispersion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices promise a broad range of biomedical and chemical applications due to their potentials of small volume requirement, short analysis and diagnostic time, high sensitivity, and high throughput analysis [1][2][3]. Recently, particular attention has been paid to droplet-based (digital) microfluidic devices since droplets isolated in immiscible oil or air can be free from cross-contamination and dispersion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Song et al [17], Damean et al [18], Niu et al [19], Sun et al [20], Wang et al [21] and Agresti et al [22] reported systems to generate sequences of droplets scanning concentrations of one substance (up to four orders of magnitude) and used them to screening of biochemical reactions. Miller et al [23] demonstrated a microfluidic system that exploits Taylor-Aris dispersion to create a concentration gradient within about 10,000 droplets per compound.…”
Section: Introductionmentioning
confidence: 99%
“…Combining integrated microfluidic technologies [16][17][18][19][20][21][22][23][24][25] with a supramolecular synthetic strategy, [15,[26][27][28][29][30] we demonstrate herein a high-throughput approach for formulating and screening multifunctional supramolecular nanoparticles (MFSNPs) that are capable of simultaneous delivery of gene and functional proteins with superb efficiency and controllable stoichiometry among individual payloads ( Figure 1). As illustrated in Figure 1a, this approach utilized two microfluidic systems including a digital droplet generator (DDG; Supporting Information, Section 1.2-1.5, video available in Supporting Information) [20,22] and a microfluidic cell culture array [31,32] .…”
mentioning
confidence: 99%
“…As illustrated in Figure 1a, this approach utilized two microfluidic systems including a digital droplet generator (DDG; Supporting Information, Section 1.2-1.5, video available in Supporting Information) [20,22] and a microfluidic cell culture array [31,32] . To enable the capability of on-chip synthesis of MFSNPs using the DDG, we developed a modular assembly system based on the supramolecular synthetic strategy [15,[26][27][28][29][30] (Figure 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation